1975
DOI: 10.1017/s0003356100030750
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary concentrations of digestible energy on the performance and carcass characteristics of early-weaned pigs

Abstract: Fifty-four pigs weaned at 3 weeks of age were allocated at an average weight of 5-4 kg to two experiments to examine the effects of diets having digestible energy (DE) concentrations ranging from 2910 to 3940 kcal/kg. In the first experiment pig growth performance and the dry-matter digestibility of the experimental diets were measured between 3 and 8 weeks of age. The composition of the carcass at 8 weeks of age was correlated with the composition of various carcass joints. In the second experiment pig growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

1981
1981
1998
1998

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 14 publications
2
4
1
Order By: Relevance
“…The DE effects seen in this trial were similar to those reported in the literature (Campbell, 1987;1975;Whittemore, 1993) where more highly concentrated diets resulted in faster growth and higher NDR and LDR than lower energy diets. According to Campbell (1987) and Whittemore (1993), increasing the DE content of the diet of the young pig while simultaneously maintaining the lysine/DE ratio of the diet is similar to the pig having been given (or voluntarily consuming) more food.…”
Section: Digestible Energy Concentrationsupporting
confidence: 87%
See 1 more Smart Citation
“…The DE effects seen in this trial were similar to those reported in the literature (Campbell, 1987;1975;Whittemore, 1993) where more highly concentrated diets resulted in faster growth and higher NDR and LDR than lower energy diets. According to Campbell (1987) and Whittemore (1993), increasing the DE content of the diet of the young pig while simultaneously maintaining the lysine/DE ratio of the diet is similar to the pig having been given (or voluntarily consuming) more food.…”
Section: Digestible Energy Concentrationsupporting
confidence: 87%
“…DLWG ranged from 410 to 640 g/day in this study while Nam and Aherne (1994) reported a range of DLWG of the order of 550 to 621 g/day when similar diets to those in this study were given. The daily food consumption levels observed in this trial were higher than the values of 700 to 790 g/day reported by Campbell et al (1975) for pigs from 5-4 to 20 kg live weight given a diet containing 15-2 MJ/kg DE while they are lower than the values of over a 1000 g/day reported by Nam and Aherne (1994) for pigs from 91 to 25-7 kg live weight given diets containing from 13-3 to 14-7 MJ/kg DE. Efficiency of food utilization was generally better for the pigs on this trial than the values of 1-87 to 1-63 kg food per kg gain reported by Nam and Aherne (1994).…”
Section: Growth Performance and Body Compositioncontrasting
confidence: 85%
“…This resulted in a curvilinear increase in the fat : protein ratio of daily gain and, therefore, in body-fat content at 19 kg. Conversely, the levels of energy intake tested by Campbell et al (1975), which ranged from approximately 3-2 to 40 M, would be expected to have only a small effect on body-fat content. It is also evident from this curvilinear relationship between energy intake and body fat, that a relatively large restriction in energy intake, from that achieved with feeding ad libitum, is required to produce a significant reduction in body fat.…”
Section: Regression Of Rate Of Protein Retention On Protein Intakementioning
confidence: 98%
“…For example, Stanier, Sanz Sampelayo and Close (1979) reported that raising the energy intake of pigs growing between 14 and 35 days of age by 0-50 and 100 increased body fat by 0-39 and 0-63 respectively; whereas Campbell et al (1975) reported that a 0-30 increase in energy intake for pigs growing from 5-5 to 20 kg had no discernible effect on body-fat content as assessed by linear backfat measurements. This resulted in a curvilinear increase in the fat : protein ratio of daily gain and, therefore, in body-fat content at 19 kg.…”
Section: Regression Of Rate Of Protein Retention On Protein Intakementioning
confidence: 99%
See 1 more Smart Citation